Oral Ulcer Healing Activity of Lemon Pepper Ethanol Extract Gel in Streptozotocin-Induced Diabetic Wistar Rats - Veranyca Chiuman; Linda Chiuman; Dian Soraya Tanjung; Mourent Miftahulaila; Suci Erawati; Florenly Florenly (Majalah Kedokteran Bandung, 2022)
Diabetes mellitus (DM) is a metabolic condition where the body's ability to produce and utilize insulin is impaired; thus, wound healing process is slower than usual in patients with DM. Lemon pepper has both antioxidant and anti-inflammatory properties. This study aimed to investigate the effect of topical application of lemon pepper fruit ethanol extracts on the healing process of oral traumatic ulcers in diabetic rats. This study was performed at the Pharmacology Laboratory, Faculty of Medicine, Universitas Prima Indonesia from September 2021–October 2021. Thirty males diabetic Wistar rats were thermally injured on the lower labial mucosa and divided into five groups: control, standard, and lemon pepper gel 5%, 7.5%, and 10% groups. The ulcer size was measured after injury and on the 7th and 14th day. On the last day, all rats underwent both routine blood count and histology study for oral ulcer tissue. On the 14th day, all treatment groups showed some significant difference wound contraction, with the highest tendency of wound contraction seen in both lemon pepper gel 10% and standard groups (62.50%. p-value =0.001). The improvement of wound contraction was also supported by reduced white blood cell count (p-value<0.05) in routine blood count and regeneration of epidermis and dermis tissues in the histology study. Hence, it can be concluded that the lemon pepper extract gel in all concentrations has good physical stability and the lemon pepper gel with the highest concentration group presents the best ulcer healing activity compared to other concentrations and has similar ulcer healing activity as the standard group that receives Kenalog® in Orabase.